Analisis dampak keberadaan wisata edukasi kampung coklat terhadap perubahan perekonomian masyarakat di Desa Plosorejo Kabupaten Blitar - Dewi, Velina Sari; Mukhlis, Imam (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze the educational conditions of the chocolate village and analyze the impact of the existence of chocolate village educational tourism on changes in the economy of the people of Plosorejo Village, Blitar Regency. This study uses qualitative data types and qualitative data with samples of educational tourism in Kampung kuning and the surrounding community who work around educational tourism in Kampung kuning. Data analysis from observations, interviews and documentation was carried out by transcribing the interview data from the manager of the Kampung Chocolate Educational Tourism and the surrounding community, then coding on the themes according to the research title. To test the validity of the data in this study, the technique used is using triangulation techniques. The conclusion in this study is that this Kampung Chocolate Educational tour, is very influential on the community, especially in encouraging the economy of the Plosorejo Village community, can provide job opportunities and job opportunities for the community. In the beginning, people who did not have jobs, worked odd jobs, farmers, and former thugs could work as employees at the Chocolate Village Educational Tour and could open up business opportunities. With job opportunities, the wheels of motion would also decrease.